2021
DOI: 10.32479/ijeep.10897
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Green Technology Development in Kazakhstan

Abstract: Although Kazakhstan is a fossil fuel rich country, policymakers desire to develop a green and sustainable economy and to contribute to the global energy transition. To understand the overall situation in green technology development in the industrial sector, we conducted the first countrywide study in Kazakhstan. In this paper, we present the results of the large survey on the use of "green technologies" by industrial companies in every region of the country. We aggregate the 380 reported cases of the use of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The processing of "boiler" dust yields 1-1.5 thousand tonnes/year of phosphorus-potash fertilisers. There is also the introduction of a GHG emissions accounting system, thanks to which emissions are reduced by 18-21 thousand tonnes of carbon dioxide per year by reducing the consumption of natural gas during the production of phosphorite agglomerate ( Abdildin et al, 2021). The general trend, with the exception of some positive examples, is generally opposite to the objectives set in the Strategy and other documents, which does not contribute to reducing greenhouse gas emissions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The processing of "boiler" dust yields 1-1.5 thousand tonnes/year of phosphorus-potash fertilisers. There is also the introduction of a GHG emissions accounting system, thanks to which emissions are reduced by 18-21 thousand tonnes of carbon dioxide per year by reducing the consumption of natural gas during the production of phosphorite agglomerate ( Abdildin et al, 2021). The general trend, with the exception of some positive examples, is generally opposite to the objectives set in the Strategy and other documents, which does not contribute to reducing greenhouse gas emissions.…”
Section: Resultsmentioning
confidence: 99%
“…Therewith, the share of environmental innovations from 2014 to 2018 decreased from 12.7% to 7.8% in the total number of innovations. A study on the introduction of green technologies by enterprises of Kazakhstan in the context of industries and regions conducted by Abdildin et al (2021) showed that the main sources of emissions (mining, metallurgical, oil, and gas industries) reduced the number of green technologies used.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the projected hydropower market may surpass 1,200 GW of global capacity and $36.3 billion in investments in 2022 (Abdildin et al, 2021). Coal and natural gas have been the chief main conventional energy used for decades.…”
Section: Figure 4 Current Trend and Prospect Of Hydropower Energymentioning
confidence: 99%
“…The development of "green" hydrogen holds significant importance for Kazakhstan, particularly in light of its trading partnership with the European Union (EU) and the EU's Green Deal. The EU's emphasis on green products and higher tariffs on non-green products will have a substantial impact on Kazakhstan's economy, making the development of "green" hydrogen crucial in the medium and long term (Abdildin 2021).…”
Section: The Possibilities For the Development Of Green Hydrogen Ener...mentioning
confidence: 99%